Precipitating causes of acid reflux episodes in ambulant patients with gastro-oesophageal reflux disease. Issue 4 (April 1995) - Barham, C P; Gotley, D C; Mills, A; Alderson, D
Abstract : Previous studies of the mechanisms that precipitate acid reflux episodes have used short term hospital based measurements. A 24 hour pH and motility recording system, incorporating a sphincter monitoring device, has been developed to study naturally occurring acid reflux episodes in control subjects and patient groups with different grades of oesophagitis. Lower oesophageal sphincter relaxations related to episodes of acid reflux were common in control subjects (67% of episodes) but became more difficult to detect as the grade of oesophagitis increased (grade 0/1 - 67%, grade 2/3 - 35%, grade 4 - 13%). A variety of events that produced recognisable transdiaphragmatic pressure patterns were associated with acid reflux episodes. In control subjects 74% of acid reflux episodes were precipitated by belching but this mechanism became less evident as the grade of oesophagitis increased (grade 0/1 - 43%, grade 2/3 - 40%, grade 4 - 29%). Activities that produced a pressure gradient across the diaphragm became increasingly important as events precipitating acid reflux as oesophagitis became more severe (controls–2%, grade 0/1 - 15%, grade 2/3 - 11%, grade 4 - 22%). This study has shown the pressure events surrounding acid reflux in fully ambulant patients with gastro-oesophageal reflux disease.